Taxonomic Partition Suggests a High Degree of Coevolution Between Termites and Their Termitophiles - Eloi, Igor; Pires-Silva, Carlos M.; Zilberman, Bruno (Sociobiology, 2021)
Termites have a tight interaction with their social parasitic Corotocini beetles. This association is thought to be mainly host-specific, despite some host-switch events. By analyzing the taxonomic partition between species and genera of Corotocini, we propose the hypothesis that the main driver of the diversity of these termitophiles is coevolution.